Effect of Repeated Intravitreal Ranibizumab and Aflibercept Injections on the Cornea in Patients with Age-Related Macular Degeneration. (9th June 2020) - Urban, Beata; Szwabowicz, Magdalena; Bakunowicz-Łazarczyk, Alina
Abstract : Purpose . To assess the effect of repeated intravitreal ranibizumab injections (RI) and aflibercept injections (AI) on the corneal endothelium and central corneal thickness (CCT) in patients with age-related macular degeneration (AMD). Materials and Methods . In the retrospective study, 110 eyes of 106 patients, aged 52 to 93 years, were analyzed. Fifty eyes were treated only with RI (I group), and 60 eyes were treated only with AI (II group). Every patient received one intravitreal injection of 0.5 mg of ranibizumab once a month or 2 mg of aflibercept for 3 subsequent months. Each patient received only 3 injections during the whole observation period. Corneal analysis was obtained with the specular microscope. Examinations were performed before initial treatment, after each injection, and 6 months after the first injection. Analysis included corneal endothelial cell density (ECD), hexagonal cell percentage (% Hex), coefficient of variation (CoV), and CCT. Results . There was a statistically significant ECD loss, regardless of the type of the anti-VEGF agent. The mean ECD value in the I group was 2397 ± 459 cells/mm 2 before RI, 2389 ± 459 cells/mm 2 after the first RI, 2386 ± 467 cells/mm 2 after the second RI, 2378 ± 475 cells/mm 2 after the third RI, and 2357 ± 460 cells/mm 2 6 months after the first RI. The mean ECD value in the II group was 2448 ± 493 cells/mm 2 before treatment, 2456 ± 498 cells/mm 2 after the first AI, 2426 ± 496 cells/mm 2 after the second AI, 2402 ± 488 cells/mm 2 after the third AI, and 2348 ± 473 cells/mm 2 6 months after the first AI. In comparison with the group treated with RI, the group treated with AI presented a greater ECD loss at each measuring point. The percentage of hexagonal cells was decreased in both groups. There was a slight increase in polymegathism in both treated groups. Ranibizumab proved to cause a small increase in CCT, while CCT remained unchanged in the aflibercept group. Conclusions . Repeated intravitreal injections of 0.5 mg of ranibizumab or 2 mg of aflibercept can influence the morphology of the corneal endothelium but not CCT.